2010
DOI: 10.1002/app.32151
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, mechanical and morphological properties of thermoplastic vulcanizates based on high impact polystyrene and styrene‐butadiene rubber

Abstract: Thermoplastic vulcanizates (TPVs) based on high impact polystyrene (HIPS)/styrene-butadiene rubber (SBR) blends were prepared by dynamic vulcanization technique. The rheological, mechanical and morphological properties of the dynamically vulcanized blends were investigated systematically. As determined by capillary rheometer, the apparent viscosity of the blends decreases as the shear rate increases, indicating obvious pseudoplastic behavior. At low shear rate, the apparent viscosity of these blends is conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The results indicate that the formation of the semi-IPN structure benefits the mechanical strength of the membranes. However, the increased percent of the PS results in the decreased elongation at break of the membranes as PS is less flexible and similar result has been reported [42,43].…”
Section: Mechanical Propertiessupporting
confidence: 75%
“…The results indicate that the formation of the semi-IPN structure benefits the mechanical strength of the membranes. However, the increased percent of the PS results in the decreased elongation at break of the membranes as PS is less flexible and similar result has been reported [42,43].…”
Section: Mechanical Propertiessupporting
confidence: 75%
“…Normally, the mechanical strength of the TPVs was mainly determined by the matrix resin. 24 When TPV was subjected to a compressive stress for the first time, the plastic deformation of HDPE matrix would generate and result in the large energy consumption and relatively high residual deformation, as shown in Figure 7(b). When the external force was removed, the plastic deformation of TPV during the compression process could only partially recover and the residual deformation would be accumulated with increasing loading–unloading cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Adhikari et al [9] also showed that rubber particle surface treatment can improve compound properties, while increasing particle size will make them worse. Wang et al [10] produced a TPV from high-impact polystyrene (HIPS) and styrene-butadiene rubber (SBR). The unvulcanized SBR compound was dispersed in HIPS using a two-roll mill mixer and SBR vulcanization was performed during compounding.…”
Section: Introductionmentioning
confidence: 99%